The Genus Lophiolepis Is at Least as Well Supported as Afrocarduus, Afrocirsium, and Nuriaea. Comment on Moreyra et al. African Mountain Thistles: Three New Genera in the Carduus-Cirsium Group. Plants 2023, 12, 3083 - Emanuele Del Guacchio; František Zedek; Paolo Caputo; Duilio Iamonico; Petr Bureš (Plants)
Moreyra and co-authors, in their recent paper published in Plants, presented a desperately needed Hyb-Seq phylogeny of the genus Cirsium sensu lato. Through their findings, they provided a critical assessment of an earlier proposal of ours to separate Cirsium sect. Eriolepis and Cirsium italicum into the genera Lophiolepis and Epitrachys, respectively. While we fully respect their right not to accept our proposal, we cannot remain silent to their arguments that not only misinterpret our findings and statements but are often in direct conflict with their own results that actually support our proposal to segregate Lophiolepis. In addition, as Moreyra and co-authors did not include Epitrachys italica (formerly Cirsium italicum) in their analyses; they have no basis for arguing in favour or against our proposal to separate it as a monotypic genus. Finally, we conclude that the genus Cirsium, as circumscribed by the above-mentioned authors (i.e., including Lophiolepis), is definitively not monophyletic.